PENGELOLAAN TAMAN MENTERI SUPENO DALAM MENDUKUNG KEBIJAKAN RUANG TERBUKA HIJAU DI KOTA SEMARANG - Priambodo, Reza Ario; ., Kushandayani; Widayati, Wiwik (Journal of Politic and Government Studies, 2014)
This study entitled Management of Parks Minister Soepeno to made policyGreen Open Space in Semarang City. Parks Minister Soepeno planned not only asan active park with planting large trees such as kranji acid in large quantities tobecome a city park . issues raised are How to Management of Parks MinisterSoepeno to made Green Open Space in Semarang City ?The purpose of this study is to investigate Management of Parks MinisterSoepeno to made policy Green Open Space in Semarang City.This research is qualitative - descriptive . Qualitative research seekinganswers to questions by examining various social settings and the individuals wholive it . The nature of the research in this paper is a descriptive analytical .Based on the results of research and discussion, it can be concluded that the Minister Supeno Park is one of the potential park owned by the city of Semarang. Because Parks Minister Soepeno is one of the few active park city park owned by the city of Semarang active . The existence Parks Minister Soepeno / Wildlife KB in terms of both policy and green open spaces , actually has met three (3) main function of 8 (eight) function space, which functions as an Environmental Park (Passive Activity) land with vegetation that has hard as lungs of the city and flower plants , function as Playground/Public Space that provides an area to play for the kids , so this park next to a neighborhood park also serves as a playground , as well as function as a place SportsÂ